Intrathecal Fentanyl versus Intrathecal Dexmedetomidine as an Adjuvant to Isobaric Levobupivacaine 0.5% in Elective Cesarean Sections: A Randomized Control Trial - Mohamed Basith; Dilip Kumar Govindan; T. Krishna Prasad; Amin Hanan; K Soundarya Priyadharsini (Journal of the Scientific Society)
Background: When a cesarean section is performed, it is crucial to have access to good postoperative analgesia. To achieve this, adjuvants are added along with local anesthetics as it has a synergistic action to improve its duration and quality. Alpha-2 adrenoceptor agonists and opioids such as dexmedetomidine and fentanyl, respectively, are used for their sedative, analgesic, and perioperative sympatholytic and cardiovascular stabilizing effects with reduced anesthetic requirements. The purpose of this research is to evaluate the effects of intrathecal fentanyl versus dexmedetomidine combined with levobupivacaine on postoperative analgesia and hemodynamic changes. Materials and Methods: This is a prospective randomized control trial, among 50 patients undergoing elective cesarean section. Group 1 will receive 0.5% levobupivacaine 2 ml + fentanyl 25 mcg and Group 2 will receive 0.5% levobupivacaine + dexmedetomidine 5 mcg. Duration of analgesia and onset and duration of sensory-motor block, perioperative analgesic requirements, sedation, and hemodynamic stability were compared. The data were entered into Microsoft Excel and analyzed using SPSS 16. Results: The baseline characteristics such as age and gender, weight, height, and body mass index were not statistically significant in both the groups. Duration of analgesia was significantly longer in the dexmedetomidine group than the fentanyl group. The mean time of onset of motor block in the group, for which dexmedetomidine was 14.23 ± 1.85 min and it was found to be much earlier than the local anesthetic group. All the patients in the dexmedetomidine group had a Visual Analog Scale (VAS) score of 0 (no pain) at the end of 4 h. In contrast, only 21 patients in the fentanyl group had a VAS score of 0, and four patients had a VAS score of 2, indicating mild pain requiring no treatment. Conclusion: The study showed that both fentanyl and dexmedetomidine as an adjuvant to levobupivacaine in cesarean section showed a longer duration of analgesia with increased sedation score and lesser pain score. When comparing the both, dexmedetomidine to the levobupivacaine has a more effective effect on postoperative pain management than fentanyl.